2022
DOI: 10.1177/00222437221078522
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Consumers with Environmental Sustainability Initiatives: Consumer Global–Local Identity and Global Brand Messaging

Abstract: Environmental sustainability is a common practice of global brands, with 90% of the top 100 Interbrand global brands making statements about environmental efforts on their websites. In this research, we explore how a consumer’s global-local identity can affect consumer engagement with a global brand’s environmental sustainability initiative. Specifically, we examine consumer engagement in response to environmental messaging based on regulatory focus, spatial construal, and temporal construal. We theorize and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…Personal values, self-transcendence and altruism are important antecedents (Follows and Jobber, 2000). Universal values are associated with global lifestyles and connectedness in cultural identities (Salnikova et al, 2022)…”
Section: Second Phase (2009-2016)mentioning
confidence: 99%
See 1 more Smart Citation
“…Personal values, self-transcendence and altruism are important antecedents (Follows and Jobber, 2000). Universal values are associated with global lifestyles and connectedness in cultural identities (Salnikova et al, 2022)…”
Section: Second Phase (2009-2016)mentioning
confidence: 99%
“…Personal values, self-transcendence and altruism are important antecedents (Follows and Jobber, 2000). Universal values are associated with global lifestyles and connectedness in cultural identities (Salnikova et al , 2022). Findings show that more globally oriented consumers tend to amplify their green materialism tendencies and are more responsive to green messaging.…”
Section: Evolution Of Research and Thematic Clustersmentioning
confidence: 99%
“…Although one person can have both identities simultaneously, one identity will still be dominant and thus has a greater impact on human behavior, depending on individual characteristics and specific situations (Ng et al, 2021). Research has indicated that consumers with a strong global identity have concerns about the environment because they can easily relate to one unifying global cause of protecting the planet's environment (Salnikova et al, 2022). In our context, a local identity activates residents' mental associations with people in the local community and climate change within their community, whereas a global identity activates associations with people around the world and climate change worldwide.…”
Section: The Moderating Role: Global-local Identitymentioning
confidence: 99%
“…regionally-based brands, luxury brands, etc.) and price sensitivity, but more recently, studies linked to social issues, such as environment and corporate social responsibility, have been conducted (Puncheva-Michelotti et al ., 2018; Bonaiuto et al ., 2002; Salnikova et al ., 2022). Global identity associated with more contextual and holistic thinking, for instance, appears to have had a more positive effect on new consumption activities (Nie et al ., 2022).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%